# What are x,y and z? x+y=-3 x+z=-2 xy+yz+xz=2

justaguide | Certified Educator

calendarEducator since 2010

starTop subjects are Math, Science, and Business

We have to solve the equations:

x + y = -3 ...(1)

x + z = -2 ...(2)

xy + yz + xz = 2 ...(3)

From (1)

x + y = -3

=> y = -3 - x

From (2)

x + z = -2

=>...

(The entire section contains 101 words.)

check Approved by eNotes Editorial

giorgiana1976 | Student

First, we'll multiply the 1st and the 2nd equations:

(x+y)(x+z) = (-3)*(-2)

We'll remove the brackets:

x^2 + xz + xy + yz = 6

We notice that the sum xz + xy + yz can be replaced by the 3rd equation:

x^2 + 2= 6

x^2 = 6-2

x^2 = 4

x1 = 2 and x2 = -2

We'll substitute x1 in the 1st equation:

2 + y = -3

y = -2-3

y = -5

We'll substitute x1 in the 2nd equation:

2  +z = -2

z = -4

We'll substitute x2 in the 1st equation:

-2 + y = -3

y = -1

We'll substitute x2 in the 2nd equation:

-2 + z = -2

z = 0

The pairs of solutions are: (2 ; -5 ; -4) and (-2  ;-1 ; 0).

check Approved by eNotes Editorial